Fundamentals of collection development and management - Johnson, Peggy 1948- (ALA Editions, 2018)
Johnson has revised and freshened this resource to ensure its timeliness and continued excellence. Consideration is given to traditional management topics, cooperative collection development and management, licenses, negotiation, and other purchasing and budgeting topics, and the ways that changes in information delivery and access technologies continue to reshape the discipline.